THE EFFECTS OF EXPLOSIVE LIMB MUSCLE STRENGTH, EYE-FOOT COORDINATION AND SELF-CONFIDENCE IN SHOOTING SKILLS - Rahmansyah, Beriman; Jufrianis, Jufrianis; Tangkudung, James (Program Pascasarjana Universitas Negeri Jakarta, 2018)
This path analysis analysis aims to obtain information about the effects of explosive limb muscle strength, eye-foot coordination and self-confidence in shooting skills in soccer athletes in the Middle School / Ragunan State High School (TRADU) and athletes in DKI Jakarta Sport Achievement Center Jakarta. This study uses a quantitative approach, survey method. The subjects in this study were Soccer Athletes at the Ragunan Middle School / Middle School High School Education Center (Special for Sportsmen) and as many as 40 Academic Development Centers for DKI Jakarta. Sampling is done by using Purposive Sampling techniques.Based on the hypothesis test, this study concludes that there is a positive influence between Leg Muscle Explosion Power on Shooting Skills in Soccer Athletes in the Middle School / Ragunan Public High School Education Center (Special For Sportsmen) and DKI Jakarta Achievement Sports Center Athlete at 8.50%. There was a positive influence between Eye-Foot Coordination with Shooting Skills on Soccer Athletes in the Middle School / Ragunan Public Education and Training Center (Special For Athletes) and DKI Jakarta Achievement Sports Center Athlete at 6.24%. There is a positive influence between Confidence and Shooting Skills on Soccer Athletes in the Middle School / Ragunan Public Education and Training Center (Special for Athletes) and Jakartas Achievement Sports Center Athlete at 7.30%. There is a positive influence between the Explosive Power of the Leg Muscles to Self-Confidence in Soccer Athletes in the Middle School / Ragunan Education and Training Center (Special for Athletes) and the DKI Jakarta Achievement Sports Center Athlete 4.94%. There is a positive influence between Foot-Eye Coordination on Self-Confidence in Soccer Athletes in the Middle School / Ragunan National Education and Training Center (Special for Athletes) and DKI Jakartas Achievement Sports Center Athlete at 5.76%. There is a positive influence between Leg Muscle Explosion Power on Eye-Foot Coordination in Soccer Athletes in the Middle School / Ragunan Middle School Education and Training Center (Special For Sportsmen) and DKI Jakartas Achievement Sports Center Athlete at 3.94%. Keywords: Limb Muscle Power, Eye-Foot Coordination, Confidence, and Football Shooting Skills